3D effects of soil-atmosphere interaction on infrastructure slope stability - Tsiampousi,A (EDP Sciences, 2023)
It has long been established that pore water pressure (pwp) variations affect the stability and serviceability of slopes. Pwp variations may be due to consolidation/swelling processes within soils of low permeability or may be due to seasonal evapotranspiration and precipitation processes. The simultaneous study of such phenomena and of hydro-mechanical coupling in sloping ground requires use of advancednumerical methods. Often, infrastructure slopes are considered in plane strain (two-dimensional) conditions for simplicity and to date this is the case for most numerical analyses considering soil-atmosphere interaction. However, this approach makes it impossible to study the longitudinal extent of a possible slip surface forming following vegetation removal. Three-dimensional, fully-coupled numerical analyses of acut slope were performed herein to study the effect of vegetation clearance on stability and explore numerically ways of implementing effective vegetation management.